Sacred Darkness : A Global Perspective on the Ritual Use of Caves - Moyes, Holley (Book collections on Project MUSE., 2013)
In this book, contributors use archaeological evidence as well as ethnographic studies of modern ritual practices to envision the cave as place of spiritual and ideological power that emerges as a potent venue for ritual practice. Covering the ritual use of caves in Europe, Asia, Australia, Africa, Mesoamerica, and the US Southwest and Eastern woodlands, this book brings together case studies by scholars whose research spans from the Paleolithic period to the twenty-first century. These contributions demonstrate that cave sites are as fruitful as surface contexts in promoting the understanding of both ancient and modern religious beliefs and practices.